Post-Mortem Interval of Human Skeletal Remains Estimated with Handheld NIR Spectrometry - Verena Maria Schmidt; Philipp Zelger; Claudia Wöss; Christian Wolfgang Huck; Rohit Arora; Etienne Bechtel; Andreas Stahl; Andrea Brunner; Bettina Zelger; Michael Schirmer; Walter Rabl; Johannes Dominikus Pallua (Biology, 2022)
Estimating the post-mortem interval (PMI) of human skeletal remains is a critical issue of forensic analysis, with important limitations such as sample preparation and practicability. In this work, NIR spectroscopy (NIRONE® Sensor X; Spectral Engines, 61449, Germany) was applied to estimate the PMI of 104 human bone samples between 1 day and 2000 years. Reflectance data were repeatedly collected from eight independent spectrometers between 1950 and 1550 nm with a spectral resolution of 14 nm and a step size of 2 nm, each from the external and internal bone. An Artificial Neural Network was used to analyze the 66,560 distinct diagnostic spectra, and clearly distinguished between forensic and archaeological bone material: the classification accuracies for PMIs of 0–2 weeks, 2 weeks–6 months, 6 months–1 year, 1 year–10 years, and >100 years were 0.90, 0.94, 0.94, 0.93, and 1.00, respectively. PMI of archaeological bones could be determined with an accuracy of 100%, demonstrating the adequate predictive performance of the model. Applying a handheld NIR spectrometer to estimate the PMI of human skeletal remains is rapid and extends the repertoire of forensic analyses as a distinct, novel approach.